Azetidine synthesis by La(OTf)3-catalyzed intramolecular regioselective aminolysis of cis-3,4-epoxy amines - Kuriyama, Yuse; Sasano, Yusuke; Iwabuchi, Yoshiharu (Frontiers in Chemistry, 2023)
Azetidine is a prevalent structural motif found in various biologically active compounds. In this research paper, we report La(OTf)3-catalyzed intramolecular regioselective aminolysis of cis-3,4-epoxy amines to afford azetidines. This reaction proceeded in high yields even in the presence of acid-sensitive and Lewis basic functional groups.